INTERNATIONAL LEGAL FRAMEWORK OF THE ARCTIC POLICY OF THE PEOPLE’S REPUBLIC OF CHINA - E. V. KIENKO (Московский журнал международного права, 2018)
INTRODUCTION. The article contains analysis of the main international legal documents on which the Arctic policy of the People’s Republic of China is based. Particular attention is paid to the international legal cooperation between China and the Arctic States, which is focused on protecting the environment, scientific research and navigation in the Arctic Ocean. The first results of the PRC’s activity in the Arctic Council as a permanent observer are also considered.MATERIALS AND METHODS. Study materials include international bilateral and multilateral agreements concluded between the People’s Republic of China and the Arctic States, as well as legal documents of the Arctic Council and researches of foreign scientists, including scientists from the People’s Republic of China, concerning the legal regime of the Arctic, legal basis for the interstate cooperation on protection of the marine environment, economic and scientific issues. General scientific and private scientific methods of cognition composed methodological basis for the study.RESEARCH RESULTS. In the course of the study, the author reveals the concepts developed by the Government of the People’s Republic of China and set out in the new initiative project “One belt – one road”, in which the Arctic plays a major role. The author analyzes international bilateral agreements between the People’s Republic of China and the Arctic States, aimed at strengthening of intergovernmental ties and developing of interstate cooperation in the field of environmental protection, navigation and scientific research in the Arctic. Furthermore, the author relates the results of the activities of the People’s Republic of China as a permanent observer in the Arctic Council. The author emphasizes that the People’s Republic of China does not pursue an aggressive Arctic policy, does not violate customary or conventional rules of International Law.DISCUSSION AND CONCLUSION. In this article, the author draws attention to the peculiarities of the formation of the Arctic component in the Chinese policy, based on international bilateral and multilateral agreements. It is brought out that China has its specifics in terms of the legal framework of the Arctic policy. The Arctic policy of the People’s Republic of China is aimed at expansion of its national interest in the Arctic. Therefore, China has developed new legal term – “near Arctic State” and issued Guidebooks for Chinese Shipping in the Northern Sea Route and in the North-West passage.